DAMPAK PEMBERITAAN PENYEBARAN COVID-19 TERHADAP PENGELOLAAN HUTAN SUMATERA BARAT - Jusmalinda Jusmalinda; Ferdinal Asmin (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2020)
Covid-19's reporting through various media has had various impacts on development activities in West Sumatra, including in forest management. Covid-19 can be assessed as a disaster, which shapes people's perceptions of the risks. This study aims to determine the impact of reporting the spread of Covid-19 on social, economic, and ecological aspects of forest management in West Sumatra. The approach used is a quantitative approach through data collection using Google Form to respondents from social forestry activists, government officials, environmental activists, and community forestry entrepreneurs in West Sumatra. The analysis in this study uses descriptive statistical analysis. The results showed that the reporting of the spread of Covid-19 had shaped perceptions of risks to health, social activities and economic activities of the community. Related to the risks to forest management, the possible impacts are reduced institutional activity from farmers / forest farmer groups, decreased income of forest farmer families, and increased disruption to forest sustainability. The government needs to encourage community empowerment through forestry extension, the development of forestry-based economic activities, and efforts to sustainably forests and land rehabilitation to reduce the social, economic and ecological impacts